Registration of 'Sequoia' Hard Red Winter Wheat. Issue 3 (25th May 2017) - Carter, A. H.; Jones, S. S.; Lyon, S. R.; Balow, K. A.; Shelton, G. B.; Burke, A.; Higginbotham, R. W.; Schillinger, W. F.; Chen, X. M.; Engle, D. A.; Morris, C. F.
Abstract : Stand establishment and emergence from deep planting are important traits for winter wheat ( Triticum aestivum L.) cultivars produced in the US Pacific Northwest. The objective of this research was to develop an adapted winter wheat cultivar with a long coleoptile and the ability to emerge well from deep planting conditions in the dryland (<300 mm annual precipitation) regions of Washington State. 'Sequoia' (Reg. No. CV‐1125, PI 678966) hard red winter wheat was developed and released by the Agricultural Research Center of Washington State University. Sequoia was tested under the population designations 2J040720, 3J040720, 2J061383, 3J061383, 4J061383, and 5J061383 and experimental designation WA8180, which were assigned through progressive generations of advancement. Sequoia is a tall cultivar adapted to the low‐precipitation, rainfed wheat production regions of Washington with excellent emergence from deep planting. Sequoia has high‐temperature, adult‐plant resistance to stripe rust, average grain protein, high grain volume weight, high yield potential, and excellent end‐use quality properties.